Una nueva coral falsa del género scaphiodontophis (serpentes: colubridae) de colombia (1969)
Scaphiodontophis dugandi new species is described from northwestern Colombia. It differs from all the other species of this genus in having the grayish (buffy to light ochraceous in life) coloration intercalated between the banded patterns on the anterior part of the body and on the tail, and in having a low number of maxillary teeth: 39 to 41 (as compared to 43 to 56 in the others).  A provisional key for the recognized forms of the genus Scaphiodontophis is offered although the relationships of several forms are unclear at this stage.